Structural effects of hydrostatic pressure in orthorhombic La2-xSrxCuO4. - Takahashi, H; Shaked, H; Hunter, B; Radaelli, P; Hitterman, R; Hinks, D; Jorgensen, J (1994)
We have investigated the effect of hydrostatic pressure on the structure of orthorhombic La2-xSrxCuO4 between 1 atm and 0.6 GPa, using neutron powder diffraction. Increasing pressure causes the tilt angle of CuO6 octahedra to decrease, leading to a transition to tetragonal symmetry. There is a strong compressibility anisotropy for the orthorhombic structure. Order parameters for the transition versus pressure are consistent with Landau theory for a second-order transition. It is shown that this transition can be universally scaled over (x,T,P) space in the context of Landau theory. We conclude that Tc varies inversely with the tilt angle and is maximum for the tetragonal structure, i.e., for flat and square CuO2 planes, for this compound. © 1994 The American Physical Society.